Collection and delivery of traffic and travel information - Burton, Paul, (Research in transportation); Stevens, A. (Researcher in transportation) (IET transportation series ;, 2020)
This book is the result of a desire by a range of UK ITS professionals to record the progress in traffic and traveller information (TTI). Much of the research and development (R & D) of TTI systems in Europe has been supported by the European Union Framework R & D programmes and has been trialled in cross border projects. These developments have informed and been complementary with standardisation work in Europe and internationally. Whilst recognising this wider context, this book offers many examples of developments and deployments of TTI in the United Kingdom, which has both contributed to and benefitted from this wider international collaboration on TTI. As a key part of the TTI story, this book details the development and application of location referencing services. TTI does not exist in isolation as an application but plays an integral part in the operation of many transport services. For example, in an inter-urban road context, TTI supports the development and rollout of `smart' motorways where messages to drivers can have an immediate effect on their behaviour and help to ensure safe and efficient use of the road space. The backbone for immediate delivery of this traffic information to drivers is through the development and implementation of dynamic signage (variable message signs), which provides dynamic traffic information to road users on the UK's Strategic Road Network, but also the provision of traffic information on non-strategic roads, primarily in urban areas. As we look to the future of road travel, a current focus to improve safety and increase capacity is for vehicles to actively cooperate with the road infrastructure and, eventually, with other vehicles. This `Cooperative Intelligent Transport System' approach will use the whole spectrum of the TTI applications along with other intelligent transport technologies, particularly communications. Much of the TTI described in this book focuses on road transport because that is where most initiatives begin as there is no inherent data collection and dissemination as in railway scheduling and signalling systems. However, the traveller requires information about all forms of transport provided as a service. For example, due to privatisation of the railways and buses there has never been a greater need for integration of information (both timetabled and dynamic) to allow seamless and efficient travel, both in everyday lives and for mega-events like the Olympics. These topics are therefore addressed in a specific chapter of this book. Information being crowd-sourced and then made freely available is increasingly taking the place of more traditional collection and dissemination of data and information by public authorities. Of course, there is no such thing as free information and there is a chapter on the business models associated with social media provision of TTI. These are markedly different from the business models that had to be formed for TTI services like RDS-TMC. To some extent we can foresee the range of technologies that we have available, but how they will be applied may surprise us. It seems likely that the nature of city and town centres will change from what we experience now so that TTI may look very different. At the time of writing, we are in the midst of the COVID-19 pandemic and our society and interactions are changing our social and behavioural perspectives, probably permanently. However, the human race will always have the need to travel and TTI will always have a part to play.